Pengaruh Influencer Marketing, Word of Mouth Dan Brand Image Terhadap Purchase Intention Pada Produk Scarlett whitening (Studi Mahasiswa FEB Universitas Islam Malang Angkatan 2020) - Ulya, Naylia Fadhilatul; Sunaryo, Hadi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to identify the influence of Influencer Marketing, Word of Mouth, and Brand Image on Purchase Intentions for Scarlett Whitening products. The sample used in this research uses the Snowball sampling technique, which is a data source sampling technique which at first is small in number, over time it becomes large and to determine the sample size using the Slovin formula which has a sample size of 82 samples used in the results of this research as well as showing There is a significant positive influence between Influencer Marketing, Word of Mouth and Brand Image variables on Purchase Intentions for Scarlett Whitening products. Likewise, the Influencer Marketing, Word of Mouth and Brand Image variables have a partial and simultaneous influence on the Purchase Intention variable for Scarlett Whitening products. Keywords: Influencer Marketing, Word of Mouth, and Brand Image